Identification of discrete functional domains of HIV-1 integrase and their organization within an active multimeric complex. - Engelman, A (1993)
HIV-1 integrase protein possesses the 3' processing and DNA strand transfer activities that are required to integrate HIV DNA into a host chromosome. The N-, C-terminal and core domains of integrase are necessary for both activities in vitro. We find that certain pairs of mutant integrase proteins, which are inactive when each protein is assayed alone, can support near wild type levels of activity when both proteins are present together in the reaction mixture. This complementation implies that HIV-1 integrase functions as a multimer and has enabled us to probe the organization of the functional domains within active mixed multimers. We have identified a minimal set of functional integrase domains that are sufficient for 3' processing and DNA strand transfer and find that some domains are contributed in trans by separate monomers within the functional complex.